(NsLOWO DO SLOWA (B- (NWESELA ROZMOWA(B. (NoPOW)QÆDANNQ(B, (NKAZKI(B, (NWÆR[Æ(B, (NBAJKI(B, (NPRIPOWÆDNIKI(B, (NPRISLÆW(B'(NQ(B, (NPRIKAZKI(B, (NNARODNÆ USMÆ[KI (B:s)E (NDLQ MOLOD[OGO [K)QÆLXNOGO WÆKU (B/s)E - (NkA^ALOWA(B, (Nt)QÆNA(B,s)E; (NaRTEM^UK(B, )Qæ(NGOR(B,s)E; (N~AJKOWSXKIJ(B, (NbOGDAN(B,s ((NkI)QÇW (B:s)E (NwESELKA(B,s, 1994)
(NtWORI WIZNA^NIH MAJSTR)QÆW UKRAÇNSXKOGO GUMORU (B- (NKLASI^NOGO J SU^ASNOGO(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NfOLXKLORs -- (NuKRA)QÇNAs)E; (NgUMORs; (NOPOW)QÆDANNQs)E; (NKAZKIs; (NW)QÆR[Æs)E; (NBAJKIs; (NPRISL)QÆW(B'(NQs)E; (NPRIKAZKIs; (NNARODN)QÆ USMÆ[KIs)E